Importance of phenotype estimation for Krabbe disease with a newly developed diagnostic procedure in the era of advanced medical treatment - Sakai, Norio (Journal of Laboratory and Precision Medicine, 2017)
Krabbe disease is one of the metabolic leukodystrophies caused by dysfunction of the hydrophobic lysosomal enzyme, galactocerebrosidase (EC 3.2.1.46) which is encoded by the GALC gene. Krabbe disease was first reported as a clinical entity 100 years ago, in 1916, by Knud Krabbe (1). The disease frequency is about 1/100,000–1/200,000 (2). It is recognized as one of the predominant genetic diseases, showing leukodystrophy from infancy to adulthood.